Question
upstudy study bank question image url

Solve: \( \begin{array}{l}3 x=y+4 \quad \text { and } \\ y^{2}-x y=9 x+7 \\ \text { Simultaneously }\end{array} \)

Ask by Medina Hall. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solutions are \( x = \frac{9}{2} \) and \( y = \frac{19}{2} \), or \( x = \frac{1}{3} \) and \( y = -3 \).

Solution

We are given the system of equations: \[ \begin{cases} 3x = y + 4 \\ y^2 - xy = 9x + 7 \end{cases} \] **Step 1: Express \( y \) in terms of \( x \) from the first equation.** \[ 3x = y + 4 \implies y = 3x - 4 \] **Step 2: Substitute \( y = 3x - 4 \) into the second equation.** \[ (3x - 4)^2 - x(3x - 4) = 9x + 7 \] **Step 3: Expand and simplify the equation.** \[ 9x^2 - 24x + 16 - 3x^2 + 4x = 9x + 7 \] \[ 6x^2 - 20x + 16 = 9x + 7 \] \[ 6x^2 - 29x + 9 = 0 \] **Step 4: Solve the quadratic equation \( 6x^2 - 29x + 9 = 0 \).** Using the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \): \[ a = 6, \quad b = -29, \quad c = 9 \] \[ x = \frac{29 \pm \sqrt{841 - 216}}{12} = \frac{29 \pm \sqrt{625}}{12} = \frac{29 \pm 25}{12} \] This gives two solutions: \[ x = \frac{54}{12} = \frac{9}{2} \quad \text{or} \quad x = \frac{4}{12} = \frac{1}{3} \] **Step 5: Find the corresponding \( y \) values.** Using \( y = 3x - 4 \): 1. If \( x = \frac{9}{2} \): \[ y = 3 \left( \frac{9}{2} \right) - 4 = \frac{27}{2} - 4 = \frac{19}{2} \] 2. If \( x = \frac{1}{3} \): \[ y = 3 \left( \frac{1}{3} \right) - 4 = 1 - 4 = -3 \] **Final Solutions:** \[ \left( x, y \right) = \left( \frac{9}{2}, \frac{19}{2} \right) \quad \text{and} \quad \left( \frac{1}{3}, -3 \right) \] **Answer:** After simplifying, the solutions are (9⁄2, 19⁄2) and (1⁄3, –3).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

To solve the system of equations \[ \begin{aligned} 1) & \quad 3x = y + 4 \\ 2) & \quad y^2 - xy = 9x + 7 \end{aligned} \] we can first express \(y\) from the first equation: \[ y = 3x - 4. \] Now, substitute \(y\) in the second equation: \[ (3x - 4)^2 - x(3x - 4) = 9x + 7. \] Expanding \((3x - 4)^2\): \[ 9x^2 - 24x + 16. \] Now substituting into the second equation, we get: \[ 9x^2 - 24x + 16 - (3x^2 - 4x) = 9x + 7. \] This simplifies to: \[ 9x^2 - 24x + 16 - 3x^2 + 4x = 9x + 7. \] Combining like terms on the left side: \[ 6x^2 - 20x + 16 = 9x + 7. \] Now, move all terms to one side: \[ 6x^2 - 20x - 9x + 16 - 7 = 0, \] which gives: \[ 6x^2 - 29x + 9 = 0. \] Next, we can use the quadratic formula \(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\) where \(a = 6\), \(b = -29\), and \(c = 9\): Calculate the discriminant: \[ b^2 - 4ac = (-29)^2 - 4(6)(9) = 841 - 216 = 625. \] Now apply the quadratic formula: \[ x = \frac{29 \pm \sqrt{625}}{2(6)} = \frac{29 \pm 25}{12}. \] Calculating the two possible values for \(x\): 1. \(x = \frac{54}{12} = \frac{9}{2} = 4.5\) 2. \(x = \frac{4}{12} = \frac{1}{3}\) Now, substitute back to find the corresponding \(y\) values for each \(x\): 1. For \(x = 4.5\): \[ y = 3(4.5) - 4 = 13.5 - 4 = 9.5. \] 2. For \(x = \frac{1}{3}\): \[ y = 3\left(\frac{1}{3}\right) - 4 = 1 - 4 = -3. \] Thus, the solutions are: \((x, y) = (4.5, 9.5)\) and \((x, y) = \left(\frac{1}{3}, -3\right)\).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy